Revival of the Faculty of Law in Belgrade immediately after the end of the Second World War - Pantić Dragan D. (Anali Pravnog Fakulteta u Beogradu)
The Faculty of Law in Belgrade was a reputable institution of higher education between the two world wars. The occupation of the country disrupted its work and the building was seized by the occupation troops. This paper presents the strenuous exertions and difficulties following the revival efforts of the Faculty of Law in Belgrade after the liberation. The preparations designed to revive the work of the Faculty began immediately after the liberation of the city in October 1944. Furthermore, numerous problems had to be solved such as accommodation, teaching staff, lack of textbooks, etc. The great self-sacrifice of the teaching staff and non-teaching personnel created conditions that enabled the Faculty of Law in Belgrade to re-open the doors to the students by the beginning of November 1945.